Associação do Malnutrition Universal Screening Tool (MUST) e Avaliação Global Subjetiva Produzida pelo Próprio Paciente (AGS-PPP) com a sobrevida e caquexia em pacientes com câncer avançado - Machado, Andressa Miranda (2023)
Cancer is a global public health problem with increasing incidence. Prognostic prediction is important because it determines which interventions and treatments will be carried out, evaluating the benefits and side effects that these will cause in the patient. Malnutrition is related to a worse prognosis in patients with advanced cancer. In addition to malnutrition, the presence of cancer cachexia is common, which is also related to a worse prognosis. Therefore, studies are needed to verify which tools are associated with the diagnosis of the nutritional status of advanced cancer patients and whether they are associated with cachexia and survival. Objectives: To associate nutritional status using MUST and PG-SGA with survival and cachexia in advanced cancer patients. Material and methods: Between 2020 and 2022 81 advanced cancer patients were evaluated. Nutritional status was assessed using the MUST, which classified patients into (MUST=0: low risk of malnutrition, MUST=: medium risk of malnutrition, MUST≥2: high risk of malnutrition) and using the PG-SGA classifying in the following categories (A = well-nourished, B = moderately malnourished or suspected of malnutrition, C = severely malnourished). Cachexia classification was carried out following Fearon and Colleagues (2011) protocol. Generalized Mixed Models (GLzM) were used to evaluate the association between MUST, PG-SGA and cachexia. Cox regression analysis was used to evaluate the relationship of MUST and PG-SGA with survival. Results: A statistically significant association was found between MUST and cachexia (p<0.001; X²=249.35). PG SGA and the MUSTxPG-SGA interaction had no significant association with cachexia (p=0.95, X² = 0.10 and p=0.78, X² = 1.750, respectively). In univariate analysis, advanced cancer patients at high risk of malnutrition (MUST 2) and severely malnourished (PG-SGA) are associated with shorter survival (hazard ratio [HR] 2.232 and p = 0.028; HR 2.510 and p = 0.030, respectively). Conclusion: MUST is associated with cachexia and is a good survival predictor, being closely related with cachexia when compared to PG-SGA, being an important tool for nutritional assessment and survival prediction in patients with advanced cancer.